PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SAYURAN ORGANIK DI SANAK BAHUMA BALIKPAPAN - Kusuma, Eka; prihandoyo, C.Prihandoyo (MEDIA RISET EKONOMI [MR.EKO], 2026)
The purpose of this study was to determine the influence of consumer behavior partially on purchasing decisions. The data used are sources that already exist, both internal and external data, and the data can be accessed through the internet and information publications. Methods of data analysis using Validity Test, Reliability Test, Classical Assumption Test, t Test. The results of the analysis show that the culture variable has a significant effect on purchasing decisions. Social variables have a significant effect on purchasing decisions. Personal variables have a significant effect on purchasing decisions. Psychological variables have a significant effect on purchasing decisions.